Volume 3B: Oil and Gas Applications; Organic Rankine Cycle Power Systems; Supercritical CO2 Power Cycles; Wind Energy 2014
DOI: 10.1115/gt2014-25475
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Three-Dimensional Unsteady Real-Gas Flows Within a Transonic ORC Turbine

Abstract: In this paper we investigate the three-dimensional unsteady real-gas flows which occur within Organic Rankine Cycle (ORC) turbines. A radial-inflow turbine stage operating with supersonic vane exit flows (M ≈ 1.4) is simulated using a RANS solver which includes real-gas effects. Steady CFD simulations show that small changes in the inducer shape can have a significant effect on turbine efficiency due to the development of supersonic flows in the rotor. Unsteady predictions show the same trends as the steady CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The fluid-dynamic losses in the stator are significantly larger than those in the rotor, confirming the results reported in Ref. [9] for a medium power capacity ORC radialinflow turbine. More in detail, the major loss contribution in the stator is due to the wake mixing downstream of the vane TE, while the fluid dynamic penalty in the rotor is mainly due to endwalls dissipation, secondary flow-induced mixing and tip-leakage flow.…”
Section: 22supporting
confidence: 89%
See 1 more Smart Citation
“…The fluid-dynamic losses in the stator are significantly larger than those in the rotor, confirming the results reported in Ref. [9] for a medium power capacity ORC radialinflow turbine. More in detail, the major loss contribution in the stator is due to the wake mixing downstream of the vane TE, while the fluid dynamic penalty in the rotor is mainly due to endwalls dissipation, secondary flow-induced mixing and tip-leakage flow.…”
Section: 22supporting
confidence: 89%
“…On the other hand, achieving high expansion efficiency is particularly challenging: the combined effect of high-pressure ratio (order of 30-50) and low speed of sound characteristic of organic vapors used in hightemperature ORC applications [2] leads to the design of machines with a supersonic radial stator and a transonic mixed-flow rotor, whose design is further complicated by their small dimensions. It follows that the design rules developed for more conventional radial turbines [3][4][5] are arguably inapplicable to this type of expanders, as opposed to mini-ORC radial inflow turbines for low-enthalpy applications [6] or those designed for larger power capacity, which feature moderate expansion ratios, in general not exceeding 12 [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This allowed the Prandtl-Meyer function ν to be formulated as a function of k. The nozzle designs that resulted from this model were validated using CFD, before being implemented within an ORC turbine stator. Later this design model was used to study unsteady effects in ORC turbines [24].…”
mentioning
confidence: 99%
“…As the organic fluid properties are totally different from air, these researches are mainly divided into two technical routes. One route focuses on forward design, including preliminary design of geometry parameters and aerodynamic design of blade profiles [12][13][14][15][16][17][18][19][20][21]. Dolz et al [13] propose that the pre-design of turbomachinery must take real gas equations of state into consideration, because the specific energy deviation between real gas and perfect gas can be as large as 100%, which may lead to total wrong turbine preliminary design result.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that a nozzle geometry with much higher exit-to-throat area ratio was required to obtain an efficient expansion. Wheeler and Ong [14,15] mainly focus on the radial turbine rotor flow mechanisms and geometry optimizations by the CFD tools. They suggested that small changes in the inducer shape had a significant effect on turbine efficiency due to the development of supersonic flows in the rotor.…”
Section: Introductionmentioning
confidence: 99%